2004
DOI: 10.1093/bja/aeh052
|View full text |Cite
|
Sign up to set email alerts
|

Pain on medical wards in a district general hospital

Abstract: Patients in all hospital specialities experience pain. Until the issue of pain management in medical patients is fully addressed the situation will not improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 0 publications
0
51
1
3
Order By: Relevance
“…[11][12][13][14][15][16] Surveys conducted among patients who had undergone ambulatory surgery indicated that 30% 15 to 40% 12 of patients experience moderate to severe pain following discharge.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Surveys conducted among patients who had undergone ambulatory surgery indicated that 30% 15 to 40% 12 of patients experience moderate to severe pain following discharge.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the increasing number of options available to clinicians, along with concerns about drug interactions and adverse effects of these complex drugs [1], the task of treating pain with intravenous opioids in the acute care setting can be challenging. Moreover, issues of patient dissatisfaction with pain management and iatrogenic overdose are major problems in hospitals today [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Pain is an incredibly common complaint on inpatient medical wards. This is perhaps not surprising, given that pain intensity tends to be underestimated by care providers [3]. In fact, a 2004 survey amongst patients in the acute care setting demonstrated that up to 43% of patients experienced inadequately treated pain, while 12% complained of unbearable pain during hospitalization [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations